Informal STEM learning: Examples from everyday spatial behaviors - Yang, Yingying; Conde Santiago, Sonia; Lasc, Daria; Hershkovich, Arielle; Grove, Lauren (Frontiers in Psychology, 2023)
Introduction Extensive research has shown a close relationship between spatial abilities and success in STEM disciplines because many STEM problems often require students to reason about spatial information. Everyday spatial behaviors may predate and facilitate the development of spatial skills. Therefore, the current study examined children’s everyday spatial behaviors and their associations with broader child development outcomes and individual differences. Methods Based on previous research, we developed an everyday spatial behaviors questionnaire for children (ESBQC). A total of 174 parents and their children aged 4–9 years old participated. In ESBQC, parents rated how much difficulty their children experience with different spatial behaviors, such as putting together a puzzle, retracing a route, or hitting a moving ball. Results Factor analysis revealed 8 components in ESBQC. The internal reliabilities were relatively high. ESBQC was positively correlated with age but not with sex. Furthermore, ESBQC predicted sense of direction, even after considering age and bias associated with parent reports. Discussion Our questionnaire may provide a useful tool for parents and other stakeholders to better understand everyday spatial behaviors and encourage interest and competence in spatial skills, ultimately promoting STEM learning in informal, everyday settings.